ICT and pedagogical tools for labor inclusion of people with hearing disabilities. - Buelvas Benítez, María Cecilia
ICTs as significant tools in society have allowed people with hearing disabilities, through new mechanisms, methods, and technological resources, to have the ability and the opportunity to be included in the best way in society. In the same way, the pedagogical strategies allow obtaining new knowledge and learning for cognitive development, interacting with other people, facing roles in their daily lives. However, this population does not have the necessary educational, labor and productive opportunities that are required to improve the quality of life and labor inclusion. The objective of the work is to identify the different ICT tools and pedagogical strategies that allow the labor insertion of this population. To achieve this, a literature review was made in Google Scholar of the last 5 years from the UNNESCO “deaf” thesaurus. The systematization and analysis of the information was done in a log format and in Google Drive. In conclusion, it has been identified that companies must implement action plans based on ICT tools that they attribute to satisfactorily improving the environment in their company for the deaf population.